The Urgency of Progressive Law Reform on Virtual Land Ownership in The Metaverse World - Prasetyo, Geta Ilham Adi; Sukmawati, Desi; Farizy, Budi Salman; Yustirandi, Ahmad Fahmi; Carubani, Ajie Sefi Al; Setyabudi, Ebbu; Billah, Mumtaz Mustaqim; Ramdan, Moch. Riki; Septian, Moch. Aldi; Sidik, Erik Muhammad; Ginanjar, Gingin; Nurmawatman, Nanang (Sekolah Tinggi Pertanahan Nasional, 2025)
The rapid development of the Metaverse has created new forms of property, one of which is virtual land ownership, raising questions about its recognition and protection in the Indonesian legal system. The central problem of this research is the absence of specific legal norms governing the ownership status, transfer, and protection of virtual land, which may lead to legal uncertainty and potential disputes. This study aims to analyze the legal position of virtual land ownership in Indonesia and to explore the urgency of formulating regulatory frameworks that ensure certainty and fairness for users. The research uses a normative juridical method with statutory and conceptual approaches, relying on secondary legal materials analyzed qualitatively. The findings show that while virtual land ownership in the Metaverse holds significant business potential, it currently lacks clear legal recognition within Indonesian property and contract law. As a result, users face weak protection of ownership rights and risks of exploitation in virtual transactions. The study concludes that progressive and adaptive legal norms are needed to address these gaps by formulating integrated regulations on virtual land, which would provide both legal certainty and protection for stakeholders while supporting innovation in Indonesia’s digital economy. Perkembangan pesat Metaverse telah menciptakan bentuk-bentuk kepemilikan baru, salah satunya adalah kepemilikan tanah virtual, yang menimbulkan pertanyaan tentang pengakuan dan perlindungannya dalam sistem hukum Indonesia. Permasalahan utama penelitian ini adalah belum adanya norma hukum khusus yang mengatur status kepemilikan, pengalihan, dan perlindungan tanah virtual, yang dapat menimbulkan ketidakpastian hukum dan potensi sengketa. Penelitian ini bertujuan untuk menganalisis kedudukan hukum kepemilikan tanah virtual di Indonesia dan mengeksplorasi urgensi perumusan kerangka regulasi yang menjamin kepastian dan keadilan bagi pengguna. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan perundang-undangan dan konseptual, dengan mengandalkan bahan hukum sekunder yang dianalisis secara kualitatif. Temuan penelitian menunjukkan bahwa meskipun kepemilikan tanah virtual di Metaverse memiliki potensi bisnis yang signifikan, saat ini belum terdapat pengakuan hukum yang jelas dalam hukum properti dan hukum kontrak Indonesia. Akibatnya, pengguna menghadapi perlindungan hak kepemilikan yang lemah dan risiko eksploitasi dalam transaksi virtual. Penelitian ini menyimpulkan bahwa norma hukum yang progresif dan adaptif diperlukan untuk mengatasi kesenjangan ini dengan merumuskan regulasi terpadu tentang tanah virtual, yang akan memberikan kepastian hukum dan perlindungan bagi para pemangku kepentingan sekaligus mendukung inovasi dalam ekonomi digital Indonesia.